2020
DOI: 10.1001/jamasurg.2020.0433
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Risk of a Venous Thromboembolic Event in Emergency vs Elective General Surgery

Abstract: IMPORTANCE Trauma patients have an increased risk of venous thromboembolism (VTE), partly because of greater inflammation. However, it is unknown if this association is present in patients who undergo emergency general surgery (EGS).OBJECTIVES To investigate whether emergency case status is independently associated with VTE compared with elective case status and to test the hypothesis that emergency cases would have a higher risk of VTE. DESIGN, SETTING, AND PARTICIPANTSThis retrospective cohort study used the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 42 publications
5
39
0
Order By: Relevance
“…Compared with elective surgical patients undergoing a comparable intra-abdominal procedure, emergency patients are at increased risk of venous thromboembolism (VTE) [ 131 , 132 ]. Patients should be assessed for risk with a validated tool at admission, and VTE prophylaxis (mechanical and/or pharmacologic) should be initiated as soon as possible even if surgery is planned [ 131 , 133 , 134 ].…”
Section: Resultsmentioning
confidence: 99%
“…Compared with elective surgical patients undergoing a comparable intra-abdominal procedure, emergency patients are at increased risk of venous thromboembolism (VTE) [ 131 , 132 ]. Patients should be assessed for risk with a validated tool at admission, and VTE prophylaxis (mechanical and/or pharmacologic) should be initiated as soon as possible even if surgery is planned [ 131 , 133 , 134 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ross et al [ 112 ] used the American College of Surgeons National Surgical Quality Improvement Program database to carry out a retrospective cohort study on 604 537 adults undergoing surgical procedures over 12 years to investigate whether emergency surgery is independently associated with VTE compared with elective surgery. They found that emergency surgery, open surgery and partial colectomy were independently associated with VTE.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, supplementary examinations should be considered for severe lower extremity varicose veins of patients with limb swelling and pigmentation. For case 3, May-Thurner syndrome can also cause lower extremity varicose veins , the surgical injury may not only induce acute deep vein thrombosis [ 22 , 23 ]. but also may cause varicose vein recurrence due to neglect of iliac vein compression syndrome.…”
Section: Discussionmentioning
confidence: 99%